2021
DOI: 10.1126/scitranslmed.abd8034
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to isolate the effects of fasting and energy restriction on weight loss and metabolic health in lean adults

Abstract: Intermittent fasting may impart metabolic benefits independent of energy balance by initiating fasting-mediated mechanisms. This randomized controlled trial examined 24-hour fasting with 150% energy intake on alternate days for 3 weeks in lean, healthy individuals (0:150; n = 12). Control groups involved a matched degree of energy restriction applied continuously without fasting (75% energy intake daily; 75:75; n = 12) or a matched pattern of fasting without net energy restriction (200% energy intake on altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 67 publications
3
104
1
2
Order By: Relevance
“…According to several meta-analyses, both IF and CR interventions produced similar changes in body weight, fat mass, fat-free mass and waist circumference [ 7 , 34 , 35 , 39 , 40 , 41 ], provided that the adherence to interventions is similar [ 7 , 40 , 41 ]. However, a recently published study, imposing a relatively tightly matched degree of energy restriction, has reported that ADF induced lower fat and greater fat-free mass loss (~−0.74 kg and ~−0.75 kg, respectively) than an isocaloric continuous daily CR (~−1.75 kg and ~−0.03 kg, respectively) during 3 weeks in 12 lean healthy adults [ 42 ]. Further research with a larger sample size and implementing isocaloric interventions in people with overweight/obesity is needed to unravel the effects of IF regimens on body composition, as compared to continuous daily CR.…”
Section: Impact Of If On Cardiometabolic Healthmentioning
confidence: 99%
“…According to several meta-analyses, both IF and CR interventions produced similar changes in body weight, fat mass, fat-free mass and waist circumference [ 7 , 34 , 35 , 39 , 40 , 41 ], provided that the adherence to interventions is similar [ 7 , 40 , 41 ]. However, a recently published study, imposing a relatively tightly matched degree of energy restriction, has reported that ADF induced lower fat and greater fat-free mass loss (~−0.74 kg and ~−0.75 kg, respectively) than an isocaloric continuous daily CR (~−1.75 kg and ~−0.03 kg, respectively) during 3 weeks in 12 lean healthy adults [ 42 ]. Further research with a larger sample size and implementing isocaloric interventions in people with overweight/obesity is needed to unravel the effects of IF regimens on body composition, as compared to continuous daily CR.…”
Section: Impact Of If On Cardiometabolic Healthmentioning
confidence: 99%
“…If intermittent fasting concepts were compared with energy-restricted diets for 3 months (10 studies; 719 people) or longer (3 to 12 months; 4 studies; 279 people), this difference in weight loss is lost [ 50 ]. The energy restriction causes the positive effect of intermittent fasting on weight loss, not fasting as a stand-alone intervention [ 51 , 52 ].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Besides weight loss, fasting-specific effects on metabolic regulation or cardiovascular health are discussed. In lean persons, there is no statistically significant difference between daily energy restriction and alternate-day fasting with or without energy restriction concerning postprandial indices of cardio-metabolic health, gut hormones, or the gene expression in subcutaneous adipose tissue [ 51 ].…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Recently, a 3-week randomized trial, which is among the first to disentangle the effects of alternate-day fasting and “traditional” daily energy restriction, revealed that alternate-day fasting without energy restriction is not sufficient to reduce body weight in lean individuals. However, although alternate-day fasting with 25% reduced energy intake reduces body mass, the decrease of body fat content is lower compared to a matched traditional daily energy restriction and confers no additional short-term metabolic or cardiovascular benefits ( 36 ). Further studies with larger cohorts and longer duration are warranted to examine the fasting-specific effects of alternate-day fasting and intermittent fasting, and directly compare their effects to diets that only reduce daily net calories.…”
Section: Dietary Approaches For Improving Cardiometabolic Healthmentioning
confidence: 99%